1998
DOI: 10.1159/000029019
|View full text |Cite
|
Sign up to set email alerts
|

Personality Patterns and Outcome in Depressive and Bipolar Disorders

Abstract: Personality traits and disorders have a strong influence on the course and outcome of depressive and bipolar disorders. Studies of the influence of personality disorders (PD) and some PD clusters on outcome of mood disorders are controversial and suggest that more specific assessment of underlying traits or dimensions is needed. Utilizing the Munich Personality test (MP-T) scales of von Zerssen, this study tries to identify specific personality traits that may influence the outcome and clinical course of unipo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
21
0

Year Published

2001
2001
2018
2018

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 34 publications
(26 citation statements)
references
References 29 publications
(39 reference statements)
3
21
0
Order By: Relevance
“…Our fi ndings are consistent with previous studies indicating that introversion may not only contribute to the onset of depression, but may also be associated with a poorer outcome for depressed patients (e.g. Heerlein et al, 1998). Our fi nding, although not formally signifi cant, that depressed patients high on social inhibition were somewhat more likely to report plans to attempt suicide, provides some support for the suggestion that introversion may be a risk factor for suicidal behaviour among depressed patients (Roy, 1998).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Our fi ndings are consistent with previous studies indicating that introversion may not only contribute to the onset of depression, but may also be associated with a poorer outcome for depressed patients (e.g. Heerlein et al, 1998). Our fi nding, although not formally signifi cant, that depressed patients high on social inhibition were somewhat more likely to report plans to attempt suicide, provides some support for the suggestion that introversion may be a risk factor for suicidal behaviour among depressed patients (Roy, 1998).…”
Section: Discussionsupporting
confidence: 92%
“…Introversion has been identifi ed as relevant to the onset, phenomenology and course of depression (Goldberg, 2001;Janowsky, 2001;Verkerk, Denollet, van Heck, van Son, & Pop, 2005). The impact of introversion on the outcome of depression is less well established, although it has been suggested that introversion may be associated with a relatively poor prognosis (Heerlein, Richter, Gonzalez, & Santander, 1998;Janowsky, 2001).…”
mentioning
confidence: 99%
“…In some ways, this finding is not surprising, because neuroticism has been shown to correlate with such a broad range of outcomes (Duggan et al, 1990;Scott et al, 1995;Heerlein et al, 1998). Thus, this finding extends neuroticism findings from unipolar depression and other psychopathologies to bipolar disorder.…”
Section: Discussionsupporting
confidence: 71%
“…Elevations of specific personality traits may induce certain maladaptive behavioral components, which increase vulnerability to symptoms of mania and depression. As described above, few studies have examined personality traits as predictors of bipolar symptoms, and results to date have been discordant (Strakowski et al, 1993;Clayton et al, 1994;Akiskal et al, 1995;Heerlein et al, 1998).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation